PENGETAHUAN KELUARGA TENTANG FAKTOR PENYEBAB DAN PENCEGAHAN DIABETES MELITUS - Dina Alviyanti; Amelia Dini Anggraini Silalahi (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Diabetes (DM) or also known as diabetes mellitus is a chronic metabolic disorder caused by the insulin hormone in the body that cannot regulate blood sugar levels effectively, causing an increase in blood sugar levels. This study aims to increase public awareness about the causes and impacts of diabetes. The research method uses a "Descriptive Survey". The population in this study was 32 people who did not have diabetes mellitus sufferers in Punggulan Village, Air Joman District, the sampling technique used Purposive Sampling technique, which means sampling based on certain considerations made by the researcher himself, based on the characteristics or properties of the population that have been known previously, so that the number of samples was 32 respondents. The results of research on the causes and prevention of diabetes mellitus based on the level of knowledge about the factors causing diabetes mellitus showed that the "sufficient" category had a value of 5.45 and a percentage of 60%. On the other hand, the level of knowledge about the prevention of diabetes mellitus was also found in the "sufficient" category, with a value of 5.7 and a percentage of 63.33%. It is recommended that the public always be informed about the causes of diabetes mellitus and how to prevent it, as well as reduce consumption of foods and other activities that can increase the risk of developing the disease.